Prevención de Caídas: Soluciones para su hogar: FCS2228-Span/FY858, rev. 7/2010 - Martin, Leigh Ann; Minton, Emily (EDIS, 2010)
Revised! FCS2228-Span, a 3-page fact sheet by Leigh Ann Martin and Emily Minton, is the Spanish language version of FCS2228/FY734 Fall Prevention: Solutions for Your Home. It lists possible hazards in your home for people growing older and modifications that can be made to prevent falls. Published by the UF Department of Family, Youth and Community Sciences, July 2010. FCS2228-Sp/FY858: Prevención de Caídas: Soluciones para su hogar (ufl.edu)